2008
DOI: 10.1007/s11269-008-9372-3
|View full text |Cite
|
Sign up to set email alerts
|

Equity in Domestic Water Rates Design

Abstract: Water rates seek at once to fund the service, to distribute the cost among users and to allocate water based on demand. Therefore, rates design is frequently subject to normative criteria such as full cost recovery, efficiency, equity and simplicity. This paper, proposes a method of ensuring the operational effectiveness of the equity criterion. Specifically, the objective is to resolve the problem of equity caused by pricing systems involving stepwise increments in the cost of aggregate household consumption.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
38
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(40 citation statements)
references
References 32 publications
(26 reference statements)
0
38
0
Order By: Relevance
“…The use of a variable fee can increase the households' efforts at water conservation by way of water saving behaviors and financial investments in water [62]. However, increasing block tariffs can have serious equity effects on households [30]. Promoting efficient use of water resources requires greater rationality in the water tariff structure [63]; however, the absence of a national regulatory body makes this difficult.…”
Section: Efficiency and Sustainabilitymentioning
confidence: 99%
“…The use of a variable fee can increase the households' efforts at water conservation by way of water saving behaviors and financial investments in water [62]. However, increasing block tariffs can have serious equity effects on households [30]. Promoting efficient use of water resources requires greater rationality in the water tariff structure [63]; however, the absence of a national regulatory body makes this difficult.…”
Section: Efficiency and Sustainabilitymentioning
confidence: 99%
“…Similarly, an analysis of water pricing in Sao Paulo, Brazil showed that increasing-block pricing favored low income households, while a flat price favored higher income earners [26]. Others argue against increasing-block pricing based on inequity [27] and evidence to suggest that it is only marginally effective in reducing water consumption [28,29]. Although variable, linear-or increasing-block pricing is widely used in OECD countries [27].…”
Section: Review Of the Literaturementioning
confidence: 99%
“…Others argue against increasing-block pricing based on inequity [27] and evidence to suggest that it is only marginally effective in reducing water consumption [28,29]. Although variable, linear-or increasing-block pricing is widely used in OECD countries [27]. This implies that increases in water pricing are predominantly driven by a need to lower water use rather than cost recovery.…”
Section: Review Of the Literaturementioning
confidence: 99%
See 2 more Smart Citations